Rede social de portadores de transtorno mental de um município de pequeno porte - Barbosa, Guilherme Correa [UNESP]; Galera, Sueli Aparecida Frari; Moreno, Vânia [UNESP]; Oliveira, Márcia Aparecida Ferreira de (My University, 2014)
This study aimed to know the available social network of mental patients from a mental-health community service in a small town. It was a qualitative study that utilized a semi-structure interview as data collection tool. The analysis of data allowed the building of two empiric categories: the mental patient in his primary network and in his secondary network. It was concluded that the patients have their family members as the main resource of social support and also establish relation- ships with their several existing scenarios in the community of their surroundings.

O estudo objetivou conhecer a rede social disponível de portadores de transtorno mental de um serviço de saúde mental comunitário de um município de pequeno porte. Trata-se de uma pesquisa qualitativa, que utilizou como instrumento de coleta uma entrevista semi estruturada. A análise dos dados permitiu-se construir duas categorias empíricas: o portador de transtorno mental em sua rede primaria e em sua rede secundária. Conclui-se que os portadores possuem como principal recurso do suporte social os seus familiares e também estabelecem relação ao seu entorno com os diversos cenários existentes na comunidade.
Social network of mental patients in a small town
Keywords: Social network; Mental disorder; Mental health; Rede social; Transtorno mental; Saúde mental